Challenges Faced for Botulinum Toxin Injection in the Treatment of Hemifacial Spasm and Blepharospasm: Our Experience in Tribhuvan University Teaching Hospital during COVID-19 Pandemic - Rajbhandari, Reema; Yadav, Jayant Kumar; Karn, Ragesh; Ojha, Rajeev; Gajurel, Bikram (Annapurna Journal of Health Sciences, 2023)
Introduction: Hemi facial spasm (HFS) and Blepharospasm (BS) is a chronic distressing condition. Botulinum toxin (BoNT) injection is one of its treatment modality. Acquiring the injection and treating the patients overcoming the lockdown hurdles of COVID pandemic has been a major challenge. Methods: Patients who were treated at Tribhuvan University Teaching Hospital (TUTH) Outpatient Department (OPD) during the COVID pandemic in 2020 and 2021 were included in this study. Results: Out of 30 patients, 77% were female. 47% were diagnosed with BS whereas the rest with HFS. About 50% of them have had symptoms for an average of 2-5 years before receiving botulinum toxin injection. The mean Jankovic score for patients before BoNT was 2.31(SD: 0.66 range 1-4). 26 patients experienced a decrease in spasm within one week of BoNT injection and had symptomatic relief. The mean Jankovic score at week 1 was 0.63(SD: 1.09 range 1-3) and the difference was statistically significant (p